Viabilidade e eficiência de óleos essenciais no manejo do míldio da videira - Fialho, Regis de Oliveira [UNESP] (2015)
This study aimed to evaluate, under laboratory and growth chamber conditions, the fungitoxic effect of seven essential oils on Plasmopara viticola, the grapevine downy mildew pathogen. We selected essential oils from cinnamon, Eucalyptus globulus, marjoram, melaleuca, piperita mint, oregano and white thyme, in comparison with the fungicide mancozeb + metalaxyl-M. In laboratory, the experiments were performed evaluating the effect of direct contact and volatile compounds of essential oils on the P. viticola spores germination; under field conditions, the effect of essential oils was on the P. viticola spores germination applied on vine leaves in field conditions. All essential oils had the ability to inhibit spores germination of P. viticola in varying degrees, as well as by fungistatic activity. It was noteworthy that all the essential oils have chemical instability, so as the incubation time or the interval between application increases, the antifungal activity of any essential oil decreased. Cinnamon and Eucalyptus globulus essential oils were the most fungitoxic for P. viticola. Under growth chamber conditions, experiments were conducted to determine the essential oils antifungal persistence activity on P. viticola; the resistance to rain and their curative and/or preventive effect on grapevine downy mildew. All essential oils at 0.5% concentrations have antifungal activity against P. viticola, when spores inoculation occurred one and six hours after oils application. However, reduction in essential oils efficacy was found on inoculated plants after 12 and 24 hours after the application. The most efficient essential oils were from cinnamon and white thyme, which provided higher mildew control on 24 hours, inoculated plants after products application. The preventive treatment was more effective on reducing downy mildew severity. Besides the fungicide mancozeb + metalaxyl-M fungicide, the cinnamon essential oil was the most efficient in ...